Kesiapan Memasuki Sekolah Dasar pada Anak yang Mengikuti Pendidikan TK dengan yang Tidak Mengikuti Pendidikan TK di Kabupaten Kudus - Halimah, Nur; Kawuryan, Fajar (Universitas Muria Kudus, 2010)
This present study is aimed to investigate the school readiness differences between student who took pre-scholl education and not took pre-school education. Participants of this study consist of 120 students in the first class of elementary shool from different school in Kudus. This study use accidental sampling. NST (Nijmeegse Schoolbekwaamheids Test) that made by Monks, Rost, and Coffie are used to know the school readiness. t analyses were performed and get the difference coeficient t1.2 =53,405, p=0,000 (p<0,01). This result showed that there are very significant differences school readiness between student who took pre-shcool education and not took pre-school education. The student who took pre-school education have better school readiness if compare with student who not took pre-school education. This is showed by mean difference from two kind of the participant. The student who took pre-school education get the mean score 25,98 but the student who not took pre-school education only get mean score 11,25.